MiR-124-3p inhibits tumor progression in prostate cancer by targeting EZH2 - Bao-feng Song; Li-zhe Xu; Kun Jiang; Fan Cheng (Functional & Integrative Genomics, 2023)
Prostate cancer (PCa) is widespread cancer with significant morbidity and mortality rates. MicroRNAs (miRNAs) have been identified as important post-transcriptional modulators in various malignancies. This study investigated the miR-124-3p effect on PCa cell proliferation, infiltration, and apoptosis. EZH2 and miR-124-3p expression levels were measured in PCa tissues. PCa cell lines DU145 and PC3 were transfected with miR-124-3p inhibitors or analogs. EZH2 and miR-124-3p linkage was validated by conducting the luciferase enzyme reporter test. The cell viability and apoptosis were assessed by flow cytometry and MTT test. Cell movement was noted during infiltration using transwell assays. EZH2, AKT, and mTOR contents were assessed using qRT-PCR and western blotting. In clinical PCa specimens, miR-124-3p and EZH2 contents were inversely correlated. Further research has demonstrated that EZH2 is the miR-124-3p direct target. Furthermore, miR-124-3p overexpression reduced EZH2 levels and lowered cell viability, infiltration, and promoted cell death, whereas miR-124-3p silencing had the opposite effect. Overexpression of miR-124-3p decreased the phosphorylation level of AKT and mTOR, whereas miR-124-3p downregulation produced the opposite result. Our findings depict that miR-124-3p prevents PCa proliferative and invasive processes while promoting apoptosis by targeting EZH2.